Partnership Scheme Alternatives for Low-Cost Rental Public Apartment in Indonesia - Ria Asih Aryani Soemitro; Farida Rachmawati; Tri Joko Wahyu Adi; Connie Susilawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The low-cost apartment development program is one of the reliable solutions to reduce housing backlog in Indonesia, especially in some major cities, due to land scarcity and high price of land. In order to accelarate the low-cost apartment, either ownership or rental apartment, it needs the private sector’s involvement. However, it requires suitable partnership scheme to attract the private sector and to deal with the land provision problem. The objective of this study is to propose partnership scheme alternative for low-cost apartment. Interview to nine government officers (ministry and local) and three person from private sector companies have been conducted to explore the possibilities of the proposed scheme. The result shows that there two major groups of scheme alternatives, which are classified based on the land owner. The first group is the scheme, which government owns the land, while the second group is the scheme, which the land is owned by the private sector. The first group has three alternative schemes, while the second one has two alternative schemes.